2011
DOI: 10.1111/j.1460-9568.2010.07560.x
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog (Shh)-Gli signaling controls neural progenitor cell division in the developing tectum in zebrafish

Abstract: Despite considerable progress, the mechanisms that control neural progenitor differentiation and behavior, as well as their functional integration into adult neural circuitry, are far from being understood. Given the complexity of the mammalian brain, non-mammalian models provide an excellent model to study neurogenesis, including both the cellular composition of the neurogenic microenvironment, and the factors required for precursor growth and maintenance. In particular, we chose to address the question of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 60 publications
2
26
1
Order By: Relevance
“…These observations of abnormal brain development conform to studies suggesting that Shh signaling acts as a mitogen to modulate neural progenitor proliferation in both mouse dorsal brain 22 and zebrafish optic tectum. 23 …”
Section: Resultsmentioning
confidence: 99%
“…These observations of abnormal brain development conform to studies suggesting that Shh signaling acts as a mitogen to modulate neural progenitor proliferation in both mouse dorsal brain 22 and zebrafish optic tectum. 23 …”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that lack of Shh signaling disrupts dorso-ventral pattering within the neural tube in mice (Chiang et al , 1996; Murdoch and Copp, 2010). In zebrafish, inhibition of Shh signaling by using mutants that lack essential components of the Shh pathway, like Smoothen ( Smo ) and Gli , reduces neural progenitor cell proliferation in the dorsal mesencephalon (Feijoo et al , 2011). Moreover, mice with mutations in Shh and Gli show a delay in motor neuron differentiation in spinal cord, suggesting that Shh signaling is also important in neurogenesis (Oh et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…At 48 hpf wild-type c-myc expression is found in the posterior margin of the optic tectum, recently identified as an important proliferative zone in the dorsal brain of teleosts (Figure 5A, arrow) [18,19]. The mRNA can also be detected in the eye and liver (Figure 5A asterisk).…”
Section: Resultsmentioning
confidence: 89%